116k views
2 votes
??help me how to do this

??help me how to do this-example-1

2 Answers

3 votes

Answer:


\large\boxed{x=√(7^2+4^2)=√(65)}

Explanation:

Use the Pythagorean theorem:


leg^2+leg^2=hypotenuse^2

We have


leg=7,\ leg=4,\ hypotenuse=x

Substitute:


x^2=7^2+4^2\to x=√(7^2+4^2)


x=√(49+16)\\\\x=√(65)

User Victor Rodrigues
by
5.5k points
2 votes

Answer:

x = sqrt( 4^2 + 7^2)

Explanation:

They want the equation to solve the triangle

We can use the Pythagorean theorem

a^2 + b^2 = c^2

where a and be are the legs and c is the hypotenuse

4^2 + 7^2 = x^2

Take the square root of each side

sqrt(4^2 + 7^2) = sqrt(x^2)

sqrt( 4^2 + 7^2) = x

User Felwithe
by
6.0k points